Distance education learning environments during COVID-19 pandemic from student perspectives: A study in Turkish higher education - Soner Arık (Journal of Pedagogical Research, 2021)
This research aims to examine the opinions of Turkish higher education students who receive distance education compulsorily due to the COVID-19 pandemic about the distance education learning environments. The data were collected through Distance Education Learning Environments Scale-Turkish Version (DELES-TR) from 3,025 students in 75 different departments at 66 Turkish universities. The study is designed within descriptive survey method. The data were analyzed using independent t-test and one-way ANOVA tests. The results showed that students were indecisive about the distance education learning environments in general and its two sub-dimensions namely 'Personal Relevance and Authentic Learning' and 'Student Interaction and Collaboration' while they partially agreed on 'Active learning and Student Autonomy' and 'Instructor Support'. The results also showed that student opinions about Student Interaction and Collaboration differed significantly in favor of those who received distance education in online learning environments. Students reported that they would prefer online learning environments if they were given the opportunity to choose between in-person and online education, and their opinions differed significantly in favor of those who had access to the distance education via a laptop computer. Further results are discussed within the related literature and several recommendations are made accordingly.